Factors influencing the intention to purchase online on women's cosmetic product in Kuching / Nurfaridza Mohammad Amran - Mohammad Amran, Nurfaridza (2014)
The purpose of this study is to identify the factors influencing the intention to purchase online on women’s cosmetic products in Kuching, Sarawak. The research is based on 95 female respondents who bought cosmetic products through online shopping. The factors that are studied in this paper are trust, attitude, brand awareness and customer online purchase experience. The result shows that trust, attitude and customer purchase experience has significant relationship with the purchase intention. However, only trust has significant influence towards purchase intention on women’s cosmetic product in Kuching. While attitude, brand awareness and customer online purchase experience did not have significant influence towards online shopping on women’s cosmetic product.